If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -24 = 48 Reorder the terms: -24 + 12x = 48 Solving -24 + 12x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 12x = 48 + 24 Combine like terms: -24 + 24 = 0 0 + 12x = 48 + 24 12x = 48 + 24 Combine like terms: 48 + 24 = 72 12x = 72 Divide each side by '12'. x = 6 Simplifying x = 6
| -5(2q+5)+6(q-7)= | | 5xy^3-45x^3y= | | t=5t/4 | | (32-y)/4=7 | | 3y^3+2y^2+21y+14= | | y^3-5= | | 4x^2-17xy-15y^2= | | m/4=13 | | 21y^2-37y+12= | | (3x+2)(3x^2-22x+35)=0 | | 9x^3-60x^2+61x+70=0 | | 1,100*0.089=x | | 1,100=0.089x | | 3(2z-1)-3(2-3x)=12 | | (-64/125)^(-2/3) | | 2x*x-5x=100 | | -17=x-5 | | 6p+2=4+5p | | 4w^2-36wv+81v^2= | | (-64/125)^(2/3) | | (-64/125)^-2/3 | | 2(2x-1)-5+3x=x-4 | | -2(4d+1)+d=-5d+8 | | 25y^2-81x^2= | | fn+12=75-4n | | 2.4x-3=13 | | 4x+1/5=2-4-8x/3 | | 4-2v=24-8 | | 27a^2+6ay-63a-14y= | | 8d-8d-d=d | | 10(5+7x)+9(11-8x)=131 | | x^2-4r+3= |